Savoring Our Food May Save Us: Countering the Global With the Local - Zialcita, Fernando N (Archīum Ateneo, 2019)
The global market erases easily-replicable jobs because capital easily sources cheaper labor elsewhere. Endemic farm products (e.g. siling labuyo) and processed food products (e.g. nata de coco) face a crisis as increasing labor costs make products from other countries more attractive. Yet the global market does pay a premium for products that communicate a unique, locally-rooted experience. When narratives explain the particularity of a product’s locality, history, and production process, customer appreciation seems to increase. While globalization fosters homogenization, it also generates the opposite: the desire for the singular. An institutionalized system, as in Europe, which recognizes a terroir, mandates labeling according to origin, and fosters branding could protect the singular and therefore benefit our farmers. Anthropology, as the science of the concrete, can help introduce such a system, for it articulates the complex interplay of natural and human factors that shape the coming-to-be of a product. Along with the food sciences, it can furnish the food industry narratives that carve out a product’s niche. An unexpected consequence may be that anthropology could help counter the destruction of the environment. Because unrestrained capitalism values goods primarily for their low cost, it homogenizes the natural environment. Fostering an attitude that cares for the singular and the meaningful may arrest McDonaldization.